2021
DOI: 10.1016/j.jse.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory response of the supraspinatus muscle in rotator cuff tear conditions

Abstract: Background: Rotator cuff (RC) disorders involve a spectrum of shoulder conditions from early tendinopathy to full-thickness tears leading to impaired shoulder function and pain. The pathology of RC disorder is, nonetheless, still largely unknown. Our hypothesis is that a supraspinatus (SS) tendon tear leads to sustained inflammatory changes of the SS muscle along with fatty infiltration and muscle degeneration, which are threshold markers for poor RC muscle function. The aim of this study was to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The role of the macrophage is an area of emerging interest in tendinopathy and tendon healing [ 24 , 25 ]. Indeed, inflammation appears to be driven by a high number of infiltrating macrophages at the inflamed tendon site [ 24 ]. Furthermore, diseased tendons from patients with tendinopathy show an abundance of CD14 + and CD68 + activated cells [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the macrophage is an area of emerging interest in tendinopathy and tendon healing [ 24 , 25 ]. Indeed, inflammation appears to be driven by a high number of infiltrating macrophages at the inflamed tendon site [ 24 ]. Furthermore, diseased tendons from patients with tendinopathy show an abundance of CD14 + and CD68 + activated cells [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of the macrophage is an area of emerging interest in tendinopathy and tendon healing [24,25]. Indeed, inflammation appears to be driven by a high number of infiltrating macrophages at the inflamed tendon site [24].…”
Section: Establishment Of the Inflammatory Cell Model And Preliminary Investigationsmentioning
confidence: 99%
“…In this light, the role of the macrophage is an area of emerging interest in tendinopathies and in general in the healing of tendons. In fact, inflammation appears to be driven by a high number of infiltrating macrophages at the inflamed tendon site [ 47 ]. Furthermore, damaged tendons from patients with tendinopathy show an abundance of CD14 + and CD68 + activated macrophages [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, interleukin 1 beta has been tied to catabolic effects on tendons and increases COMP production 68 . Proteomic profiling demonstrated that migrating macrophages heavily influence the outcome in the initial degeneration stages 69 .…”
Section: Discussion Of Literaturementioning
confidence: 99%